Endothelial cell-specific anticoagulation reduces inflammation in a mouse model of acute lung injury - Lou Jian; Hu Yue; Wu Min-dan; Che Luan-qing; Wu Yin-fang; Zhao Yun; Tian Bao-ping; Bao Zheng-qiang; Zhu Chen; Wu Yan-ping; He Lu-lu; Bai Chun-xue; et al. (Acta Pharmacologica Sinica; Vol 40, No 6 (June 2019): Acta Pharmacologica Sinica, 2019)
Tissue factor (TF)-dependent coagulation contributes to lung inﬂammation and the pathogenesis of acute lung injury (ALI). In this study, we explored the roles of targeted endothelial anticoagulation in ALI using two strains of transgenic mice expressing either a membrane-tethered human tissue factor pathway inhibitor (hTFPI) or hirudin fusion protein on CD31+ cells, including vascular endothelial cells (ECs). ALI was induced by intratracheal injection of LPS, and after 24 h the expression of TF and protease-activated receptors (PARs) on EC in lungs were assessed, alongside the extent of inﬂammation and injury. The expression of TF and PARs on the EC in lungs was upregulated after ALI. In the two strains of transgenic mice, expression of either of hTFPI or hirudin by EC was associated with signiﬁcant reduction of inﬂammation, as assessed by the extent of leukocyte inﬁltration or the levels of proinﬂammatory cytokines, and promoted survival after LPS-induced ALI. The beneﬁcial outcomes were associated with inhibition of the expression of chemokine CCL2 in lung tissues. The protection observed in the CD31-TFPI-transgenic strain was abolished by injection of an anti-hTFPI antibody, but not by prior engraftment of the transgenic strains with WT bone marrow, conﬁrming that the changes observed were a speciﬁc transgenic expression of anticoagulants by EC. These results demonstrate that the inﬂammation in ALI is TF and thrombin dependent, and that expression of anticoagulants by EC signiﬁcantly inhibits the development of ALI via repression of leukocyte inﬁltration, most likely via inhibition of chemokine gradients. These data enhance our understanding of the pathology of ALI and suggest a novel therapeutic strategy for treatment.